Otomatisasi Sistem Pengendalian dan Pemantauan Kadar Nutrisi Air menggunakan Teknologi NodeMCU ESP8266 pada Tanaman Hidroponik - Marisa, Marisa; Carudin, Carudin; Ramdani, Ramdani (LPPM STT Terpadu Nurul Fikri, 2021)
The number of evictions of agricultural land to be used as buildings, offices and settlements has become narrow and agricultural land is reduced, so that farmers are now starting to grow a lot of crops using the hydroponic method, where this hydroponic method is a method of farming without soil elements. However, this hydroponic method requires intensive checking to monitor the condition of nutrient levels in the water so that plants grow well. This is a serious problem among hydroponic farmers because if the nutrient levels in the water do not match the needs of the type of plant, it will cause the death of the plant. Lettuce hydroponic plants require a water nutrient dose (PPM) of 560 – 840. If the PPM value exceeds the ideal value in the nutrient solution, it will result in reduced water absorption by lettuce plants so that the food formation process (photosynthesis) is disrupted. Meanwhile, if the PPM/EC value is smaller than the ideal value, the lettuce growth process will be hampered. Therefore, an automation control and monitoring system was made using the Deep Flow Technique method in adjusting the nutrient dose based on the concentration value by converting the PPM value on hydroponic plants according to the age of the plant. the system that is made can control the volume of nutrients well so as to achieve ideal nutritional conditions.